Maxillary sinus augmentation - A B Tarun Kumar; Ullas Anand (Wolters Kluwer Medknow Publications, 2015)
Placing dental implants in the maxillary posterior region can be both challenging and un-nerving for a regular implant dentist who is not well versed with advanced surgical procedures. It is vital for a general dentist to understand the fundamentals of bone grafting the maxillary sinus if he/she is really committed to providing the best health care for their patients. The dental practice is seeing an increasing group of patients who are living longer, and this group of older baby boomers often has an edentulous posterior maxilla either unilateral or bilateral. When edentulous, the posterior maxilla more likely has diminished bone height, which does not allow for the placement of dental implants without creating additional bone. Through grafting the maxillary sinus, bone of ideal quality can be created (allowing for placement of dental implants), which offer many advantages over other tooth replacement modalities. The sinus graft offers the dental patient a predictable procedure of regenerating lost osseous structure in the posterior maxilla. This offers the patient many advantages for long-term success. If dentists understand these concepts, they can better educate their patients and guide them to have the procedure performed. This article outlines bone grafting of the maxillary sinus for the purpose of placing dental implants. This review will help the readers to understand the intricacies of sinus augmentation. They can relate their patient's condition with the available literature and chalk out the best treatment plan for the patient, especially by using indirect sinus augmentation procedures which are less invasive and highly successful if done using prescribed technique.